Identification, prevalence and impacts of viral diseases of UK winter wheat - Flint, Laura J. (2014)
The potential for viruses to be causing the plateau in the yield of UK wheat (Triticum aestivum) was investigated. Mechanical inoculation of Cynosurus mottle virus to wheat cv. Scout and cv. Gladiator caused 83% and 58% reduction in the number of grains produced, highlighting the potential of viruses to cause disease and yield loss. Viruses historically detected in cereals in the UK were not found to be prevalent following real time reverse transcriptase polymerase chain reaction testing of 1,356 UK wheat samples from 2009-2012 using eleven assasys developed in the project. This included an assay for Cynosurus mottle virus, which was based on its complete genome sequence which was obtained for the first time in this project. Viruses detected were Barley yellow dwarf virus-MAV (6 samples) (BYDV-MAV), Barley yellow dwarf virus-PAV (6 samples) (BYDV-PAV) and Soil-borne cereal mosaic virus (12 samples) (SBCMV). There was a higher prevalence of viruses in the south, thought to be due to warmer temperatures which benefitted insect vectors and the molecular processes of infection. Viruses were most commonly detected in the variety JB Diego, perhaps because this variety has no known resistance to viruses. The low prevalence of known viruses could also have been because they were outcompeted or replaced by previously unknown ones. Next generation sequencing was used to test 120 samples from an organic site, including wheat, weeds and insects, to search for novel viruses. Testing of twelve storage regimes for insect traps using BYDV-PAV infected Sitobion avenae for recovery of PCR amplifiable RNA using 18S rRNA and BYDV-PAV assays found that 0.5 M EDTA was the most successful regime which was therefore used in the collection of samples for sequencing. Known viruses such as BYDV-PAV were detected along with some additional potentially novel viruses (eight possibly novel viruses or strains of viruses with four in wheat). One such virus was apparently present in 25% of all wheat samples tested, making it potentially very significant. This could be important for unlocking the yield potential of wheat because it could be a cryptic virus which is highly prevalent. In order to control the spread of viruses their methods of transmission must be understood, therefore testing of seeds and resulting plants from Cynosurus mottle virus infected material was done. Tests did not detect the virus, therefore it was concluded that seed transmission does not occur. However, further tests are required. In conclusion this study indicates that known viruses are not currently a major problem for UK winter wheat. However, novel viruses that are a problem may be detected in the future perhaps by next generation sequencing. Additonal viruses from abroad would add to the threat. The impact of all viruses in wheat may be greater in the future due to climate change.